Blessed Are the Migrant Mothers, for Theirs Will Be the Kingdom of God - Castillo-Lobos, L (UNIV ARTURO PRAT, INST ESTUDIOS INDIGENAS, 2023)
Latin American migrant mothers in Chile tend to occupy poor subsistence spaces that shape the upbringing of their childhoods in conditions that stress their expectations, resulting in uprooting and frustration. The objective is to analyze the representations of religious beliefs in the discourses of a group of migrant mothers in Santiago de Chile subjected to thematic content analysis according to the assumptions of the theology of migration. It was theorized around the categories: a bastion of hope, biblical hermeneutics, and revelation. The stories obtained enunciate the vicissitudes of migration and its resistance through faith and its relationship with God in a narrative of liberation that connects, in the salvation of God, the biblical idea of the "blessed" to establish them as a theological place, because in them the face of God is revealed, manifesting his prophetic and eschatological presence.